Rice bran protein-chitosan nanoparticle as a delivery system of ε-polylysine: preparation, characterization, antioxidant and antibacterial activity - Na Wang; Ran Xu; Xiao Lu; Yuzhuo Sun; Huifang Bu; Xiao Zhi; Wanyu Dou; Fengqing Hu; Lishuang Wang (Food Chemistry: X, 2025)
Rice bran protein (RBP)-chitosan (CS) nanoparticles as a delivery system loaded with ε-polylysine (ε-PL) were successfully synthesized by thermal aggregation-induced self-assembly technique, and the physicochemical properties and antibacterial activity were comprehensively evaluated by various techniques. The results indicated that the preparation process parameters (RBP/CS mass ratios, ε-PL concentration, pH, time, and temperature) had a significant regulatory effect on the particle size, PDI, turbidity and encapsulation efficiency of R-C-ε-PL NPs. Meanwhile, the R-C-ε-PL NPs exhibited excellent thermal stability, hygroscopicity and storage stability. And ε-PL promoted the α-helix structure to a relatively stable β-sheet structure of R-C-ε-PL NPs with a more compact molecular structure through hydrophobic interactions, hydrogen bonding, and electrostatic forces. Furthermore, R-C-ε-PL showed better antioxidant and antibacterial activities for free DPPH and FRAP radicals as well as microorganisms than RBP-CS. Overall, the results revealed that R-C-ε-PL NPs was an effective delivery system of ε-PL, and provided theoretical references for application in food preservation.